Evaluation of a Herbal Toothpaste Formulation with the Addition of Nginang Ingredients as an Antimicrobial Agent Against Streptococcus mutans - Khazari Noorin Husna Ibrahim; Rasyidah (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to determine the antimicrobial activity of herbal toothpaste formulations containing betel leaf (Piper betle L.) extract against Streptococcus mutans and to evaluate the physical characteristics of the resulting preparations. The research employed a laboratory experimental design with variations in betel leaf extract concentrations of 5%, 10%, and 15%, each conducted in four replicates. The analyses included phytochemical screening, antimicrobial activity testing using the disc diffusion method, and evaluation of the toothpaste preparations, including pH measurement, organoleptic assessment, homogeneity testing, foam formation analysis, and viscosity determination. The results of the phytochemical screening indicated that the betel leaf extract positively contained triterpenoids, flavonoids, saponins, phenolic compounds, and alkaloids. The antimicrobial activity test demonstrated that the betel leaf extract produced average inhibition zones of 16.4 mm, 22.7 mm, and 25.6 mm at concentrations of 5%, 10%, and 15%, respectively. The evaluation of the toothpaste formulations showed pH values ranging from 8.04 to 8.42, which fall within the Indonesian National Standard (SNI) range of 4.5–10.5. The preparations exhibited a semi-solid and homogeneous texture, with the highest foam height of 20.6 mm observed at the 15% extract concentration, and viscosity values within the required acceptable range. In conclusion, the herbal toothpaste formulation containing betel leaf extract demonstrated strong antimicrobial activity against Streptococcus mutans and met the required physical parameters for toothpaste preparations. Therefore, it has potential to be developed as an alternative herbal toothpaste based on traditional natural ingredients suitable for oral health applications.